Analisis Disiplin Kerja Karyawan pada PT Safemax Indonesia - Zikkra Ilham Malik; Christian Wiradendi Wolor; Adnan Kasofi (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study employs a descriptive qualitative method with the aim of describing and analyzing issues related to employee work discipline. A qualitative approach is utilized by relying on both primary and secondary data. The primary data in this research were obtained through direct field observation, interviews, and documentation of employee work activities, while secondary data were collected from books, journals, and other literature relevant to the topic of work discipline. The main data sources consist of interview transcripts with four informants, including from HRD, Project Control, and two staff at PT Safemax Indonesia. Informants were selected purposively, as they were considered to have a deep understanding of the situation and dynamics of work discipline within the company. The primary objective of this research is to understand how work discipline is implemented, the influencing factors, and the challenges faced in its application. The findings reveal that although the company has established clear standards and rules, the implementation of work discipline still faces challenges such as ineffective communication, high workload, fatigue, and external factors like weather and field conditions. These findings highlight the need for improved managerial strategies and more adaptive motivational approaches to foster a more disciplined and productive work culture.